Papua New Guinea : 2006 Article IV Consultation-Staff Report; and Public Information Notice on the Executive Board Discussion for Papua New Guinea. (IMF Staff Country Reports; Country Report ;, 2007)
This 2006 Article IV Consultation highlights that Papua New Guinea is enjoying its fourth year of recovery and macroeconomic stability, but major challenges lie ahead. Sound macroeconomic policies over the past several years have reduced fiscal vulnerabilities, lowered inflation, spurred business confidence, and boosted growth. High prices for key export commodities have strengthened the fiscal and external positions. However, progress toward achieving the country's Medium-Term Development Strategy objectives or Millennium Development Goals has been limited. Recent developments and the near-term outlook remain favorable.